2011
DOI: 10.3109/03009742.2011.586649
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rosuvastatin on subclinical atherosclerosis and arterial stiffness in rheumatoid arthritis: a randomized controlled pilot trial

Abstract: Our data suggest that rosuvastatin has a modest anti-inflammatory effect in RA patients with low disease activity in terms of reduction in DAS and fibrinogen level. Rosuvastastin may also improve subendocardial perfusion and lower the urate level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 57 publications
2
25
1
1
Order By: Relevance
“…202 Generally, it is thought that statins do not induce any improvement in arterial stiffness, yet some clinical trials have suggested that statins are beneficial in reducing arterial stiffness because of their pleiotropic anti-inflammatory effects. [203][204][205] SUMMARY Stiffening of the PAs (both large elastic and, likely, small resistance vessels) occurs in all forms of PH to some degree or another. In PH, it is still not clear whether arterial stiffening is a cause or a consequence, a question that will have to be addressed separately in all the different classes and forms of PH.…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%
“…202 Generally, it is thought that statins do not induce any improvement in arterial stiffness, yet some clinical trials have suggested that statins are beneficial in reducing arterial stiffness because of their pleiotropic anti-inflammatory effects. [203][204][205] SUMMARY Stiffening of the PAs (both large elastic and, likely, small resistance vessels) occurs in all forms of PH to some degree or another. In PH, it is still not clear whether arterial stiffening is a cause or a consequence, a question that will have to be addressed separately in all the different classes and forms of PH.…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%
“…This raised the hypothesis that the pleiotropic anti-inflammatory effects of statins may have similar benefits. Early clinical trials suggest that they may do 45,46 but absence of an antihypertensive effect of statins argues against an important improvement of arterial stiffness. 47 Benefits for statin treatment in reduction of arterial stiffness above general cardiovascular risk reduction have not been demonstrated.…”
Section: Therapeutic Interventionmentioning
confidence: 99%
“…To our knowledge only two studies have examined the SEVR in patients with RA [17,18]; one small pilot study revealed that the SEVR improved following 12 months of lipid-lowering treatment when compared with a group receiving only a placebo drug [17], while in another study the SEVR was worse following 7 weeks of anti-inflammatory treatment in RA and ankylosing spondylitis patients [18]. However, the small sample sizes of both studies, as well as the inclusion of different patient groups in the latter study, make these findings difficult to interpret.…”
Section: Introductionmentioning
confidence: 99%